Ambada hairstyle of Koli women - Mumbai Archive Project Team (Jio Institute, 2024)
The ambada is a low bun typically positioned at the nape of the neck. This is a simple and elegant hairstyle for Koli women. During festivals and celebrations, they often adorn the bun with flowers, typically jasmine, and gold ornaments to add a decorative touch.